Evaluation of a Complementary Cyber Education Program for a Pathophysiology Class - Yoo, Ji-Soo; Ryue, Sook-Hee; Lee, Jung Eun; Ahn, Jeong-Ah (Korean journal of medical education, 2009)
The goal of this study was to develop and evaluate a complementary cyber education program for a required pathophysiology class for nursing students. The cyber education program comprised electronic bulletin boards, correspondence material storage, an announcement section, a report submission section, reference sites, and statistics on learning rates. Twelve online lectures complemented five lectures in the classroom. To evaluate the course's educational effectiveness, we performed an online objective questionnaire and an open questionnaire survey anonymously, and compared the complementary cyber education program with traditional classroom education. The complementary cyber education program effected significant improvements in scores for importance with regard to major, clarity of goals and education plans for courses, professor readiness, preciseness and description of lectures, amount and efficiency of assignments, and fairness in appraisal standards compared with the traditional classroom education group. This study indicates that a complementary cyber education program provides nursing students with the flexibility of time and space, the newest information through updated lectures, efficient motivational aids through intimacy between the lecturer and students, and concrete and meaningful tasks. The complementary cyber education course also increased student effort toward studying and student satisfaction with the class.